Barriers to routine childhood vaccination during COVID-19: Lessons from a primary healthcare study in Greece - Marinetta Bakea; Despoina Gkentzi; Chrysoula Perdikogianni; Eleni Vergadi (Vaccine: X, 2025)
Background: The COVID-19 pandemic has disrupted childhood vaccination programs globally. This study aimed to evaluate the impact of the pandemic on routine childhood vaccinations in primary care settings in Greece, specifically in an area with traditionally high vaccination adherence, and identify factors influencing parental vaccination decisions. Methods: A single-center, two-part study: The first part was a retrospective observational analysis of vaccination records for children aged 0–18 years at a primary healthcare center in Crete, Greece, covering January 2019 to December 2021 (before and during the pandemic). The second part was a cross-sectional survey using parental questionnaires to explore reasons for delayed or missed vaccinations during the pandemic. Results: A total of 3027 children received 6768 vaccinations during the study period. Compared to the pre-pandemic year, vaccination visits declined by 8.1 % in the first pandemic year and 28.9 % in the second. Infants (<2 years) and adolescents (12–18 years) experienced the greatest decreases. MMR, Tdap, and MenACWY vaccinations were the most affected, whereas influenza vaccine uptake increased during the first pandemic year. The sharpest declines aligned with Greece's strict lockdown periods and surges in COVID-19-related deaths. The leading pandemic-related reasons for delayed vaccinations were fear of virus exposure (23.6 %) and movement restrictions (7.6 %). Conclusions: The COVID-19 pandemic significantly reduced routine childhood vaccinations in our area, particularly among infants and adolescents. The decline in routine vaccinations was attributed to fear of exposure and coincided with the country's strict lockdown periods and a sharp rise in COVID-19-related deaths, suggesting that both government restrictions and heightened public fear played crucial roles in delaying immunization. Notably, influenza vaccination rates increased, due to strong public health messaging and expert recommendations. These findings highlight the critical role of clear communication and safe and accessible healthcare services in sustaining immunization coverage, even during public health crises.